Maximum performance expression is affected by octopamine and antennae removal in Acheta domesticus. (30th April 2022) - Bubak, Andrew; Swallow, John; Adeola, Fadeke; Lailvaux, Simon P
Abstract: Animals in nature seldom use their maximum performance abilities, likely in part due to context-dependent differences in performance motivation. Despite interest in the factors affecting performance expression, the physiological mechanisms underlying variation in performance motivation are poorly understood. We manipulated levels of the biogenic amine octopamine (OA) to test the hypothesis that OA drives motivation to express maximum bite force in male house crickets. We also tested the effect of antenna removal on bite force given prior evidence of potential links among antennaectomy, aggression, and OA. We found that administration of an OA antagonist, epinastine, significantly decreases realized maximum bite force, as does antenna removal. In addition, the performance decrement induced by antennaectomy is abolished by administration of excess OA, and that rescue effect is itself nullified by the simultaneous administration of epinastine. These data show that OA is an important mediator of performance in insects, and thus of performance motivation, and potentially a promising candidate for the short term manipulation of performance. Abstract : We demonstrate a neuroendocrine basis to the motivation of house crickets to use their performance (i.e. athletic) abilities to their greatest extent. The reasons why animals seldom perform to their maximum performance capacities in nature are poorly understood, and tests for both performance motivation and the behavioral and physiological mechanisms underlying such motivation are rare. Our results offer insight into how animals use their performance capacities to conduct important ecological tasks.